PERILAKU PENGGUNA NARKOTIKA DI PUSAT REHABILITASI SOSIAL DAN EKONOMI YAYASAN LARAS DI KOTA SAMARINDA TAHUN 2015 - Rosdiana Rosdiana (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2016)
This study discusses the overview of the behavior of drug users. Users in 2010 as many as 340 users, 330 users in 2011 and in 2012 as many as 348 users. The aim of this study was to obtain a behavior of a rehabilitation center for drug users in the social and economic foundations of the barrel in the city of Samarinda .The method used is qualitative research methods to depict or describe the main purpose of objective circumstances.This study showed the presence of resident behavior that is not true of the drug itself , one assumes that the receipts are not narcotics then it can work properly . So this mindset is what needs to be improved. Based on the results, the conclusion that the behavior of drug users in rehabilitation centers of social and economic foundations of the barrel includes knowledge about the barrel of drug users already know the function of the foundation of the barrel and the attitude of drug users show has received and responded to baikmengenai everything in the can at the foundation of the barrel, so that drug users were enthusiastic about taking existing rehabilitation programs and supported the role of a good officer.